Upaya Meningkatkan Kemampuan Berhitung Anak Usia 5 -6 Tahun Melalui Metode Sempoa Di Paud Tunas Muda IKKT Jatimakmur – Kota Bekasi - Christina Wahyuningsih; Arie Widiyastuti; Wening Rahayu (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This research aims to improve the numeracy skills of children aged 5–6 years at PAUD Tunas Muda IKKT, Jatimakmur, Bekasi City through the use of abacus media. The research employed classroom action research (CAR) using the Kemmis & McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were 20 children in group B. Data were collected through observation, interviews, and documentation with indicators including number recognition, object counting, matching numerical symbols, as well as performing simple addition and subtraction. The results showed a significant improvement in children’s numeracy skills. In the pre-cycle, the average achievement was 46.15%; it increased to 59.23% at the end of cycle I; and reached 83.07% at the end of cycle II. Thus, the abacus proved effective in improving early childhood numeracy skills. The study recommends that PAUD teachers utilize abacus media creatively and variably in teaching early mathematics.